Genetic variations associated with adaptation in Acrocomia palms: A comparative study across the Neotropics for crop improvement - Jonathan A. Morales-Marroquín; Alessandro Alves-Pereira; Brenda Gabriela Díaz-Hernández; Suelen Alves Vianna; Carlos Eduardo de Araújo Batista; Carlos A. Colombo; José Baldin Pinheiro; Maria Imaculada Zucchi (PLoS ONE, 2025)
Population genetic research has evolved, focusing on selection processes using single nucleotide polymorphisms (SNP) genotyping techniques to study crop traits and domestication. This study explores the adaptation process of three neotropical palms of Acrocomia , a genus that has high potential for oil extraction. Our research focused on their genetic structure, evolutionary significance, and implications of the selection signatures for breeding efforts. We employed genotyping-by-sequencing (GBS) focusing on outlier SNP markers to identify adaptive genes in A. aculeata , A. totai , and A. intumescens across their entire distributions. Our results reveal two major gene pools in A. aculeata : a Central American group and a South American group, mainly influenced by dispersal and biogeographic barriers. Putative selective signatures were identified in candidate genes associated with traits related to oil biosynthesis, pathogen resistance, and adaptation to environmental stress like drought tolerance. A. totai exhibited a pronounced genetic structure influenced by distinct biomes, suggesting recent diversification driven by climatic and geological factors, particularly within the Pantanal biome. A. intumescens displays genetic structuring shaped by the endemic process of biogeographic barriers within the Caatinga biome . Correlations between allele frequencies and climatic variables highlight adaptation to diverse environments, with the annual mean temperature and precipitations being one of the most influential. Candidate genes associated with fatty acid and carotenoid biosynthesis, as well as pathogen resistance and drought tolerance, indicate targets for future breeding studies. Despite the challenges associated with reduced representation sequencing, this study highlights the potential for gene discovery in Acrocomia , offering promising targets to enhance oil yield productivity. Future efforts should prioritize whole-genome sequencing and genotype-environment interaction studies to realize the full potential of Acrocomia spp. in sustainable oil production.